Summary of the 2002 CAG Strategic Planning Survey - Philip M Sherman; Sandra M Daniels; Richard N Fedorak (Canadian Journal of Gastroenterology)
In this Journal, we have recently highlighted the progress of the Canadian Association of Gastroenterology (CAG) in meeting the goals and objectives outlined in the first Strategic Plan developed in 1993 (1). In September 2002, a Strategic Planning survey was mailed to all members of the CAG (a copy of the cover letter and survey are present for viewing on the CAG Web site www.cag-acg.org/whatsnew/strat_plann_surv.htm. The results of the responses to this survey were collated and presented to the Past Presidents of the CAG at a retreat held during the summer of 2003. These findings were then employed to develop a Strategic Plan for the CAG to guide its progress and development over the next five to ten years. A subsequent issue of this Journal will include a presentation of the CAG 2004 Strategic Plan, which was finalized and approved by the CAG Governing Board during the annual fall meeting in October 2003.